Unmet oral health needs and barriers to dental services among socially marginalized youth: a scoping review - Pranav Vaishampayan; Jaskaran Singh Beniwal; Piotr Wilk; Sarah McLean; Abbas Jessani; Abbas Jessani (Frontiers in Oral Health)
ObjectivesBarriers limiting access to oral health significantly impact dental service utilization among socially marginalized youth, often resulting in unmet needs and poor oral health outcomes. Identifying and understanding these barriers is critical to inform the development of strategies to enhance oral healthcare access for this vulnerable population. This review examines the barriers restricting access to oral healthcare and unmet dental needs among socially marginalized youth worldwide, offering insight to guide the development of targeted interventions.MethodsA comprehensive search was performed across electronic databases, including Embase, MEDLINE (Ovid), Scopus, and the Cochrane Library. Two independent reviewers screened all primary studies, irrespective of publication year, to identify relevant research on barriers to care and unmet oral health needs among socially marginalized youth. Primary studies addressing barriers to oral healthcare access and unmet needs were included, with no restrictions on publication date. Studies published in languages other than English were excluded. Any discrepancies identified during the screening process were resolved through consensus. The CLARITY tool was utilized to evaluate the risk of bias in the included studies.ResultsOf the 484 studies identified, six quantitative and one qualitative study met the inclusion criteria. The review identified multiple barriers such as financial constraints, structural impediments, and psychological factors that inhibit access to dental care facilities among socially marginalized youth. Three studies were conducted in the United States, two in Australia, and one each in the United Kingdom and Kenya. Among the identified barriers, four studies reported financial constraints and structural and logistical challenges, respectively while one study reported psychological barriers to dental care. A high prevalence of unmet needs such as dental caries and periodontal diseases, was observed within this demographic. The unmet dental needs identified in the included studies encompassed dental caries (n = 3), missing teeth (n = 2), periodontal diseases (n = 1), tooth pain (n = 1), and dental infections (n = 1). However, small sample sizes and lacking in robust study design limit the findings' generalizability, emphasizing the need for more diverse studies on oral health outcomes in socially marginalized youth.ConclusionThis scoping review identified critical research gaps in regards to access to oral health and dental service utilization among socially marginalized youth. Oral health initiatives are warranted to reduce oral health inequalities among socially marginalized youth.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/T82D3.